Children’s language abilities predict success in remote communication contexts - Erin Smolak; Karla K McGregor; Nancy Ohlmann; Nichole Eden; Ronald Pomper; Shivani Gajre; Timothy Arbisi-Kelm (Language Development Research, 2021)
Remote communicative contexts are part of everyday social, familial, and academic interactions for the modern child. We investigated the ability of second-graders to engage in remote discourse, and we determined which of several abilities—language, theory of mind, and temperament—predicted their success. Fifty 7-to-9-year-old monolingual English speakers with a wide range of language abilities participated in standardized testing and an expository discourse task in which they taught two adults to solve the Tower of London, one in simulated video chat and a second in a simulated phone condition. The discourse was scored for the inclusion of 15 items deemed relevant to the explanation. Children included from 27% to 87% of the items. They communicated more information via gesture than spoken word in both conditions. They included more spoken information in the phone condition than the video condition and more information overall in the phone condition. Performance was positively associated with spoken language ability. There was no relationship between performance and theory of mind, temperament, ability to solve the Tower of London, age, or sex. We conclude that 7-to-9-year-olds adjust the modality and content of their message to suit their remote partner's needs, but their success in remote discourse contexts varies greatly from individual to individual. Children with below-average language skills are at risk for functional impairments in remote communication.